Pengaruh Demokrasi Terhadap Perubahan Mekanisme Pemilihan Kepala Daerah oleh Dewan Perwakilan Rakyat Daerah (DPRD) - Nabella Rani (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2014)
The hallmark of a state of democracy is the implementation of the general election .The system was based on the implementation of the elections of the form of democracy there , either directly or indirectly (representatives) .The state of the unity of the republic of indonesia as an archipelago is one of the state an adherent of the popular sovereignty, namely democracy pancasila .So that all the activities of the state and government shall not contravene with the values of philosophy pancasila and still consider the constitution state that is the Undang Undang Dasar 1945.